PENGARUH KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA UD. MEMORI KABUPATEN NIAS SELATAN - Jernih Lase (Universitas Nias Raya, 2023)
Type of research used is a quantitative type that is causal. The data source was from consumers, with the population and sample in the study being as many as 34 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is simple linear regression analysis. The results of this study showed that the thitung value of 5,866>ttabel was 1,694. This research can be concluded that there is a positive and significant influence of marketing communication on purchasing decisions on UD. Memory Kabupaten Nias Selatan. (1) Interaction between employees and buyers needs to be improved through good service to consumers. (2) To improve purchasing decisions, employees should provide understanding to consumers through promotional activities. (3) The availability of goods should be very necessary to affect the consumer's decision at the time of purchase.